Consumo de alcohol y desempeño académico de los estudiantes de bachillerato de la Unidad Educativa Réplica Eugenio Espejo del cantón Babahoyo - Mora Torres, María Elizabeth (2025)
This study addresses the impact of alcohol consumption on the academic performance of high school students from the Eugenio Espejo Replica Educational Unit in Babahoyo. In our country, Ecuador, 45% of adolescents report having consumed alcohol, which affects key cognitive areas such as memory and decision-making. Al a local level, it was identified that 54% of the students evaluated show a high level lof alcohol dependence, which directly affects their academic performance and aspects such as their concentration and motivation, which are key factors in achieving educational success. The study, designed with a mixed and correlational approach, includes interviews and surveys with parents, complemented by the application of the UDIT test to students, which yieldes results that show recurrent patterns among adolescents with low academic performance such as absenteeism, disorganization and lack of emotional control, which is linked to alcohol consumption. In addition, the influence of family and social factors and social factors that normalize consumption in their home environment is shown. Teachers and adolescents recommend educational campaigns, workshops for their parents and strengthening of psychological support. The analysis highlights the need for strategic preventive interventions and mentorions programs to reduce the impact of alcohol consumption in the school environment.